Structure and Evolution of Neurexophilin - Petrenko, Alexander G. (J Neurosci, 1996)
Using affinity chromatography on immobilized α-latrotoxin, we have purified a novel 29 kDa protein, neurexophilin, in a complex with neurexin Iα. Cloning revealed that rat and bovine neurexophilins are composed of N-terminal signal peptides, nonconserved N-terminal domains (20% identity over 80 residues), and highly homologous C-terminal sequences (85% identity over 169 residues). Analysis of genomic clones from mice identified two distinct neurexophilin genes, one of which is more homologous to rat neurexophilin and the other to bovine neurexophilin. The first neurexophilin gene is expressed abundantly in adult rat and mouse brain, whereas no mRNA corresponding to the second gene was detected in rodents despite its abundant expression in bovine brain, suggesting that rodents and cattle primarily express distinct neurexophilin genes. RNA blots and in situ hybridizations revealed that neurexophilin is expressed in adult rat brain at high levels only in a scattered subpopulation of neurons that probably represent inhibitory interneurons; by contrast, neurexins are expressed in all neurons. Neurexophilin contains a signal sequence and is N-glycosylated at multiple sites, suggesting that it is secreted and binds to the extracellular domain of neurexin Iα. This hypothesis was confirmed by binding recombinant neurexophilin to the extracellular domains of neurexin Iα. Together our data suggest that neurexophilin constitutes a secreted glycoprotein that is synthesized in a subclass of neurons and may be a ligand for neurexins.